Vascular Biology Selection of Mechanisms and Clinical Applications (IntechOpen, 2020)
The two main causes of death in the world are directly related to cardiovascular system disorders, ischemic heart disease, and stroke. These pathological conditions are caused by complex molecular mechanisms related to endothelial dysfunction and, finally, structural and functional alterations of blood vessels. Clinical evidence demonstrates the relevance of knowledge about vascular biology, from molecular mechanisms to clinical applications, especially for students of medical sciences or basic sciences. This book is an international effort of collaboration, with the purpose to create an academic tool for students or people interested in learning about vascular biology. I invite the readers to check the chapters and explore the topics developed by experts in the field.